THE EFFECT OF SUSTAINABILITY REPORT QUALITY ON REVENUE GROWTH GENDER OF THE BOARD OF DIRECTORS AS A MODERATING VARIABLE - Wijaya Triwacananingrum; Sri Rembulan (Universitas Pelita Harapan, 2022)
This study aims to determine the relationship between the influence of the association between the quality of sustainability reports on revenue growth, as well as the gender diversity of the board of directors as a moderator of the relationship between the two variables. This research uses multiple regression model for the analysis tool. A sample of 146 data was collected from 73 industrial, energy, and mineral resource companies listed on the Singapore Exchange (SGX) for two periods (2018-2019). The results showed that the quality of the sustainability report had no significant effect on revenue growth. In addition, the results of this study also show that the gender diversity of the board of directors does not significantly affect the relationship between the quality of sustainability reports and revenue growth.